Carbon adsorbents synthesized from plastic waste for CO2 capture - Kaur, Simarjot (My University, 2018)
PET waste has been used to develop carbon adsorbents by direct carbonization followed by chemical activation using KOH. The textural properties of the adsorbents were studied using N2 adsorption-desorption isotherms and presence of functional groups were analyzed using XPS analysis. With chemical activated conditions it was observed that optimum sample (PET-3-700) showed highest surface area of 1428.7 m2 g-1 and total pore volume of 0.47cm3 g-1. Presence of oxygen functionalities in the sample was confirmed by XPS analysis. Fixed bed adsorption setup was used for estimating CO2 uptake capacity for adsorbents under dynamic conditions, with varying concentrations of CO2 (5-12.5%) and adsorption temperatures (30-100 °C), these conditions are relevant to flue gas conditions at industrial level. PET-3-700 under pure CO2 flow and at temperature of 30 °C produced maximum CO2 uptake capacity of 1.3 mmol g-1. Adsorbent produced was found to be completely regenerable, tested by multiple adsorptions-desorption cycles. There was decrease in adsorption capacity with increase in adsorption temperature indicating pysiosorption behavior of the adsorbent. Freundlich isotherms best described the adsorption process at different adsorption temperatures and CO2 concentrations. Further, in order to save experimentation time a model was developed and simulated, which estimated the breakthrough profiles at different experimental conditions. Hence, combining all above discussions makes the adsorbent potential material for CO2 capture for industrial and other relevant applications. Fig.1 shows schematic of overall dissertation work
Keywords: PET waste; KOH activation; CO2 adsorption; Adsorption kinetics; Adsorption isotherm; Modelling & simulation